Systematic Literature Review: Implementation of Online Learning Based on Education Levels in Indonesia - Dinata, Vania; Wedi, Agus; Fajarianto, Otto (JTP - Jurnal Teknologi Pendidikan, 2024)
The COVID-19 pandemic has significantly accelerated the adoption of online learning, prompting extensive research on its implementation across various educational levels in Indonesia. This study employs the Systematic Literature Review (SLR) method, analyzing 13 articles from the GARUDA database, published between 2019 and 2023. The findings reveal diverse platforms utilized for online learning, including Google Classroom (3 mentions), Quizizz (2 mentions), Edmodo (3 mentions), WhatsApp (2 mentions), and custom-developed platforms. At the primary and secondary education levels, platforms like Quizizz and Edmodo were associated with improvements in student motivation (42.5% increase in motivation) and learning outcomes (up to 84% in comprehension improvement for specific materials). However, challenges such as limited internet access and reduced interaction hindered learning experiences. In higher education, Google Classroom was the most frequently cited platform, enhancing accessibility and learning independence. Despite these benefits, issues such as unstable internet connectivity, skill-based material comprehension, and limited engagement persisted. This study concludes that online learning has notably improved accessibility, motivation, and learning outcomes, with significant potential to enhance educational quality. However, addressing barriers such as technical limitations and fostering better interaction are essential for further optimization. These insights provide valuable guidance for refining online learning practices and policies in Indonesia.